Role of sweet orange (Citrus sinensis) waste in lowering the meat cholesterol and fat of Padjadjaran sheep - Lovita Adriani; Elvia Hernawan; Ujang Hidayat (Jurnal Ilmu Ternak dan Veteriner, 2015)
This research is aimed to evaluate sweet orange’s role in lowering meat cholesterol and fat in Padjadjaran sheep. Twenty sheeps with body weigth 29.66±2.74 kg and variance coefficient <10% were used in this research using Completely Randomize Design (CRD). The treatments were consists of four level sweet orange addition in ration. The treatments were T1 (0%), T2 (7%), T3 (12%) and T4 (17%) that were repeated 5 times. The research was conducted for five weeks with observed variables are ration consumption that was measured everyday, body gain that was measured every week, cholesterol and triglycerides measured at the end of the research. During the research water consumption was given ad libitum. Meat samples were selected randomly from three for each repeated treatments. Observation result showed the highest decrease on meat cholesterol level was T2 treatment with 9.43±0.04 mg/mg on thigh and 9.71±0.04 mg/mg on breast. Meanwhile for fat, the highest decrease was from T4 treatment with 9.70±3.98 ug/mg dan 10.48±1.85 ug/mg. Rumen’s pH did not show significant difference (P>0.05) on all treatments with value range between 6.80±0.01 - 6.5±0.02. In conclusion, sweet orange (Citrus sinensis) waste is capable to lowering cholesterol level and fat in meat of Padjadjaran sheep. Key Words: Citrus sinensis Waste, Meat Cholesterol , Meat Fat, Padjadjaran Sheep